ANALISIS PRODUKTIVITAS TENAGA KERJA PADA PROYEK PEMBANGUNAN GEDUNG KANTOR PT. PRIMA INDOJAYA MANDIRI - Manizta, Shella; Firdaus, Firdaus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
From the results of this research, the average field productivity value was 4.41 m³/person for foundation work, 4.54 m³/person for casting work, 1,017.46 kg/person for iron work, and 14.32 m²/person for formwork work. The productivity value according to SNI is 0.938 m³/person for foundation work, 4 m³/person for casting work, 200 kg/person for steel work, and 4.24 m²/person for formwork work. Then the productivity value according to the PUPR Ministerial Decree is 0.67 m³/person for foundation work, 4 m³/person for casting work, 71.46 kg/person for steel work, 9.09 m²/person for formwork work. There are quite significant differences for all jobs when compared with the reference (SNI 7394-2008 and PUPR Ministerial Regulation 28-2016). In foundation work, the comparison of field productivity with SNI is 4.71 times and with the PUPR Ministerial Regulation is6.58 times. In casting work, field productivity with SNI and PUPR Ministerial Regulations is the same, namely 1.135 times. In steel work, the comparison of field productivity with SNI is 5.09 times and with the PUPR Ministerial Regulation is 14.24 times. In formwork work, the comparison of field productivity with SNI is 3.38 times and with the PUPR Ministerial Regulation is 1.58 times..Keywords: Labor Productivity, PermenPUPR, Indonesian National Standards